Carabelli trait in primary tooth - A case report - Rengarajan Hemamalini; Nazargi Mahabob; Gobichettipalayam Jagatheeswaran Anbuselvan; Andamuthu Yamunadevi; Muthukrishnan Sivagami; Jeyakumar Asha; Saravanakumar Anbarasu (Wolters Kluwer Medknow Publications, 2023)
The Carabelli cusp (Cusp of Carabelli) is a tubercle or the extra fifth cusp found on the mesiopalatal cusp of the maxillary permanent and deciduous molars. It is nonfunctional but it can be used to distinguish populations and is also used in forensic and anthropological studies. This condition is uncommon on deciduous teeth. In this case report, we present a rare case of unilateral presence of cusp of Carabelli in deciduous dentition.